Systematic prioritization of e-business risks in China West Africa digital cooperation using empirical evidence from Ghana - Shurong Zhao; Dennis Akomanyi Darko; Lois Tweneboah Kodua; Ailing Luo; Tiantian Sun; Albert Awortwe Sagoe; Geoffrey Bentum-Micah (Discover Sustainability)
Abstract This study examines the multifaceted risks inherent in e-business cooperation between China and West Africa, with a specific focus on Ghana, recognized as a regional digital hub and a strategic gateway for China’s digital expansion. Drawing on empirical data collected from 40 experts across Ghana’s consumer electronics, telecommunications, digital payment, and online retail sectors, the research employs a hierarchical decision model and the Best–Worst Method to systematically identify and prioritize e-business risks. Grounded in an integrated theoretical framework, the study combines Transaction Cost Theory as the primary economic lens with the Technology Acceptance Model to capture behavioral factors influencing technology adoption, and Commitment-Trust Theory to address relational and trust dynamics. This comprehensive framework provides a nuanced understanding of how institutional, technological, sociocultural, and legal risks interact to increase transaction costs and influence cross-border digital trade outcomes. The findings reveal institutional risks, particularly inadequate digital transaction regulations and insufficient data governance, as the most critical barriers, followed by technological risks such as cybersecurity vulnerabilities and infrastructure gaps. Sociocultural challenges, including language barriers and divergent consumer behaviors, as well as legal risks related to inadequate cybercrime legislation and ineffective intellectual property enforcement, significantly impact e-business sustainability. By offering a pioneering, theory-driven risk assessment framework tailored to the China–West Africa context, this study provides valuable insights for policymakers, business leaders, and investors seeking to mitigate risks, enhance trust, and foster sustainable growth in emerging digital markets. The integration of these three theoretical perspectives represents a novel contribution to the literature on international e-business risk management in emerging economies.